Exercise intolerance in patients with chronic coronary syndrome: insights from exercise stress echocardiography - Zhu, Wei-wei; Tian, Run-Yu; Guo, Di-chen; Lin, Ming-ming; Cai, Qi-zhe; Qin, Yun-yun; Ding, Xue-yan; Lv, Xiu-zhang (Frontiers in Cardiovascular Medicine, 2024)
AimsThis study applied exercise stress echocardiography (ESE) to identify risk factors associated with exercise intolerance in patients with chronic coronary syndrome (CCS).Methods and results90 CCS patients underwent a cardiopulmonary exercise test and ESE, assessing exercise capacity, left ventricular systolic and diastolic function, and systolic reserve. The patients were divided into two groups according to the percentage of predicted oxygen consumption (VO2) at peak (≥85%, normal exercise tolerance group; <85%, exercise intolerant group). The left ventricular ejection fraction, average mitral valve S’, and left ventricular global longitudinal strain were lower in the exercise intolerant group than in the normal group, but no significant differences were observed in myocardial work parameters at rest. The average mitral valve E/e’, EDVi/E/e’, and proportion of abnormal diastolic function at the peak were higher in the exercise intolerant group than in the normal group. Moreover, the ΔSVi and flow reserve were lower, but the Δaverage mitral valve E/e’ was higher in the exercise-intolerant group. From univariate and multivariate logistic regression analysis, only peak EDVi/E/e’ and ΔSVi correlated independently with exercise intolerance in CCS patients. With cutoff values of 8.64 ml/m2 for peak EDVi/E/e’ and 12.17 ml/m2 for ΔSVi, the combination of these factors had an area under the receiver operating characteristic curve of 0.906 (95% confidence interval, 0.820–0.960) for the prediction of exercise intolerance in CCS patients.ConclusionHemodynamic changes during exercise in CCS patients were effectively evaluated using ESE. An elevated peak EDVi/E/e’ and a decreased ΔSVi are independent risk factors for exercise intolerance in patients with CCS.